The Effect of Green Marketing, Brand Image, And Word of Mouth on Interest in Buying Drinking Water In Le Minerale Brand Packaging (Study on Le Minerale Brand AMDK Customers) - M Faisal Asykari; Eko Suseno Hendro Riyadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The increasingly rapid development of the industrial world has changed the human mindset that is oriented towards the industrial revolution, where life now depends on the industrial world. The existence of business expansion such as the construction of factories and the manufacture of production with a very large capacity that ignores concern for the environment will have a negative impact on the environment. The purpose of this study is to examine the effect of Green Marketing on buying interest in Le Minerale products. the type of research used is associative research with a quantitative approach. Green Marketing has no effect on buying interest. Green Marketing carried out by AMDK Le Minerale does not affect consumer buying interest. Brand Image has no effect on buying interest. The brand image carried out by AMDK Le Minerale does not affect consumer buying interest. Word Of Mouth has a significant effect on buying interest. This shows that Word of Mouth is able to encourage consumer buying interest to buy Le Minerale bottled water.